2022
DOI: 10.1088/1674-4926/43/1/013101
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the passivation, band alignment, gate charge, and mobility degradation of the Ge MOSFET with a GeO x /Al2O3 gate stack by ozone oxidation

Abstract: Ge has been an alternative channel material for the performance enhancement of complementary metal–oxide–semiconductor (CMOS) technology applications because of its high carrier mobility and superior compatibility with Si CMOS technology. The gate structure plays a key role on the electrical property. In this paper, the property of Ge MOSFET with Al2O3/GeO x /Ge stack by ozone oxidation is reviewed. The GeO x passivation mechanism b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…[7][8][9] At present, the common removal organic pollutants methods include adsorption, biodegradation and advanced oxidation processes (AOPs). AOPs are widely used in the removal of pollutants because of their high degree of oxidation and good degradation effect, AOPs can be divided into ozone oxidation, [10,11] photocatalytic oxidation (UV, visible light), [12][13][14] Fenton oxidation (homogeneous, heterogeneous) [15,16] and any combination of them. [15,17] In recent years, the photo Fenton process, which combines photocatalysis and Fenton process, has become a research hotspot of AOPs because of its strong oxidation ability and high utilization efficiency of oxidants.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] At present, the common removal organic pollutants methods include adsorption, biodegradation and advanced oxidation processes (AOPs). AOPs are widely used in the removal of pollutants because of their high degree of oxidation and good degradation effect, AOPs can be divided into ozone oxidation, [10,11] photocatalytic oxidation (UV, visible light), [12][13][14] Fenton oxidation (homogeneous, heterogeneous) [15,16] and any combination of them. [15,17] In recent years, the photo Fenton process, which combines photocatalysis and Fenton process, has become a research hotspot of AOPs because of its strong oxidation ability and high utilization efficiency of oxidants.…”
Section: Introductionmentioning
confidence: 99%
“…It offers nearly four times higher hole mobility than Si (1900-500 cm 2 Vs −1 ), so Ge FETs are of great interest for high-carrier innovative devices [3]. However, unlike SiO 2 , GeO 2 cannot be the highquality and insulating natural interface layer [4][5][6]. Recent studies have shown that the dielectric constant (k) of cubic zirconia with space group Fm 3m (c-ZrO 2 ) can be as high as 37 compared with amorphous and monoclinic ZrO 2 , due to the higher symmetry and smaller molar volume [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%